Aesthetic strategies to explore beyond the models of sustainable development: An analysis of Lisa Simpson's Musical Sewing. (25th April 2018) - Schröder, Andressa
Abstract: This essay provides a critical reflection about the (lacking) ethical dimension in the conventional models of sustainability through an aesthetic approach. To perform this exercise of reflection, the work of the Brazilian artist Lisa Simpson—Agente Costura is introduced and some "unconventional" aesthetic strategies present in her work, such as embodiment, affect, mindfulness, rhythm and movement, are explored. These aesthetic strategies are demonstrated to have the potential to enhance and improve environmental perception and generate self‐reflection, engagement and responsibility. Furthermore, the processual qualities and transformative potential of sustainability are emphasized through an investigation of the complex temporal dimensions that are combined in Simpson's practice. The work of the Agente Costura enlightens not only possible alternative paths for pragmatic and multisensorial strategies to examine environmental and sustainability ethics, but also the rich role that can be played by artists and artistic practices within the increasingly necessary inter‐ and transdisciplinary collaborations for sustainability.